(untitled) (Confluências | Revista Interdisciplinar de Sociologia e Direito, 2025)
This is a review of the book Mobilizing for Abortion Rights in Latin America, written by Mariela Daby and Mason W. Moseley. The book is part of the Cambridge Elements series and analyzes feminist mobilizations for abortion rights in Latin America, highlighting the importance of deploying massive and inclusive mobilizations to achieve political change. It begins with an overview of the shifting landscape of abortion rights, focusing on factors such as secularization, public opinion, and leftist governments. The authors include case studies such as the successful legalization of abortion in Argentina, driven by the Ni Una Menos protests, and also mention advances in Chile and Mexico, as well as setbacks in Nicaragua. The book argues that broad and unified feminist movements are essential to securing abortion rights, as demonstrated by Argentina’s experience, where abortion was framed as a social justice issue and unifying symbols like the green handkerchief were adopted. In my review, I highlight that, while the book provides valuable lessons for feminist movements globally, particularly in the United States after the overturn of Roe v. Wade, it could include a more critical analysis. To support this, I discuss the case of the decriminalization of abortion in Colombia up to 24 weeks, achieved through the unconstitutionality lawsuit filed by the Causa Justa movement, which, however, did not rely on massive protests, as well as Poland’s failures despite large-scale mobilizations. Both cases reveal the complexities of relying exclusively on popular mobilizations. I also emphasize the need for greater inclusivity in abortion rights activism, highlighting the importance of addressing the perspectives of historically excluded groups, including migrant, Indigenous, Afro-descendant, and LGBTQ+ communities. In conclusion, I suggest that the book could delve deeper into strategies to sustain movements during political or economic crises, advance reproductive rights in authoritarian contexts, and analyze both the strengths and limitations of Latin American feminist movements to offer a broader and richer perspective.